OP0093 Low runx3 expression alters dendritic cell function in patients with systemic sclerosis and contributes to enhanced fibrosis. (12th June 2018) - Marut, W.; Affandi, A.; Broen, J.; Bossini-Castillo, L.; Ottria, A.; Tieland, R.; van Bon, L.; Rossato, M.; de Kroon, L.; van Roon, J.; Martin, J.; Lafyatis, R.; et al.
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune disease with unknown pathogenesis manifested by inflammation, vasculopathy, and fibrosis in skin and internal organs. The type I IFN signature found in SSc propelled us to study plasmacytoid dendritic cells (pDCs) in this disease. Objectives: To identify candidate pathways underlying pDC aberrancies in SSc and to validate its function on pDC biology. Methods: PCR-based transcription factor profiling and methylation status analyses, SNP genotyping by sequencing, and flow cytometry analysis were performed in pDCs from healthy controls or SSc patients. pDCs were also cultured under hypoxia and RUNX3 levels were determined. To study Runx3 function in DCs, Itgax -Cre: Runx3 f/f mice were used in an in vitro functional assays and bleomycin-induced SSc skin inflammation and fibrosis model. Results: Transcription factor RUNX3 was significantly downregulated in SSc pDCs on RNA and protein levels. A higher methylation status of the RUNX3 gene correlated with RUNX3 gene expression level and disease susceptibility. After sequencing of the RUNX3 promoter region, we identified a non-synonymous SNP rs6672420 associated with SSc and hypermethylation of RUNX3 . Additionally, pDCs cultured in hypoxic conditions showed a significantly lower RUNX3 expression. Furthermore, mouse pDCs deficient of Runx3 showed enhanced expression of co-stimulatory molecules upon CpG stimulation. Finally, in SSc bleomycin model, mice with DC-specific deletion of Runx3 showed increased skin inflammation and fibrosis. Conclusions: We found low RUNX3 expression in pDCs of SSc patients. The presence of a SNP and higher methylation status of RUNX3, and downregulation in hypoxic condition, suggest at least three pathways underlying the low RUNX3 expression observed in SSc pDCs. We demonstrate a detrimental role of RUNX3-ablated DCs in a mouse SSc model further underscoring the role of pDCs in this disease. Further research is warranted to explore the potential therapeutic effect of RUNX3 targeting in fibrotic disease. Disclosure of Interest: None declared